2020
DOI: 10.1128/msphere.00949-20
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Biosynthesis of Sulfated Benzenediol Lactones with a Phenolic Sulfotransferase from Fusarium graminearum PH-1

Abstract: Total biosynthesis or whole-cell biocatalytic production of sulfated small molecules relies on the discovery and implementation of appropriate sulfotransferase enzymes. Although fungi are prominent biocatalysts and have been used to sulfate drug-like phenolics, no gene encoding a sulfotransferase enzyme has been functionally characterized from these organisms. Here, we identify a phenolic sulfotransferase, FgSULT1, by genome mining from the plant-pathogenic fungus Fusarium graminearum PH-1. We expressed FgSULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Results obtained from this study showed that A. coerulea is capable of sulfation of chalcones and exhibits parallels between microbial and mammalian metabolism not only in phase I but also in phase II metabolism [21,31]. It is widely known that the phase II sulfation reactions are mediated by the enzyme sulfotransferases, which catalyze the transfer of sulfonate group from the active sulfate to the substrates containing hydroxyl groups [45]. Thus, the sulfate metabolites of licochalcones and xanthohumol were supposed to be produced by the enzyme sulfotransferase from A. coeralea.…”
Section: Microbial Transformation Of Licochalcones a B C H And Xanthohumol By A Coeruleamentioning
confidence: 74%
“…Results obtained from this study showed that A. coerulea is capable of sulfation of chalcones and exhibits parallels between microbial and mammalian metabolism not only in phase I but also in phase II metabolism [21,31]. It is widely known that the phase II sulfation reactions are mediated by the enzyme sulfotransferases, which catalyze the transfer of sulfonate group from the active sulfate to the substrates containing hydroxyl groups [45]. Thus, the sulfate metabolites of licochalcones and xanthohumol were supposed to be produced by the enzyme sulfotransferase from A. coeralea.…”
Section: Microbial Transformation Of Licochalcones a B C H And Xanthohumol By A Coeruleamentioning
confidence: 74%
“…Like other plant SOTs, LGS1 is predicted to be localized in cytoplasm. Cytosolic SOTs contain several conserved PAPS-binding motifs, including the one interacts with 5′-phosphate of PAPS (TYPKSGT), 3′-phosphate of PAPS (YxxRNxxDxxVS), and nucleotide of PAPS (GxxGxxK/R) ( Xie et al, 2020 ). Multiple sequence alignment indicates that LGS1 contains these motifs, but with some variations (SLPKSGT and YxxRExxDxxVS, respectively) ( Supplementary Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…LGS1 contains the highly conserved histidine residues (H216) ( Landi and Esposito, 2020 ) and moderately conserved histidine residues (H317A) ( Supplementary Figure 10 ), which likely act as a base to remove the proton from the substrate hydroxyl group, thereby forming an oxygen anion, and then attacking the sulfo group of PAPS to complete the transfer of the sulfo group. To determine whether these residues play a key role in catalysis, we conducted site-directed mutagenesis on residues likely act as a catalytic base (H216A, H317A) or crucial for PAPS binding (K148A, Y247F) ( Xie et al, 2020 ). While LGS1 H 216 A (resulting strain: YSL8f, Supplementary Table 3 ) exhibited same activity as wild type LGS1, replacing LGS1 with LGS1 K 148 A , LGS1 Y 247 F , and LGS1 H 317 A in ECL/YSL8a (resulting strain: YSL8g-i, Supplementary Table 3 ) completely abolished the synthesis of 4DO and 5DS ( Supplementary Figure 11 ), implying that these residues are critical to the catalytic activity of LGS1 ( Supplementary Figure 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to other plant SOTs, LGS1 is predicted to be localized in cytoplasm. Cytosolic SOTs contain several conserved PAPS-binding motifs, including the one interacts with 5′-phosphate of PAPS (TYPKSGT), 3’-phosphate of PAPS (YxxRNxxDxxVS), and nucleotide of PAPS (GxxGxxK/R) 26 . Multiple sequence alignment indicates that LGS1 contains these motifs, but with some variations ( SL PKSGT and YxxR E xxDxxVS, respectively) (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…LGS1 contains the highly conserved histidine residues (H216) 27 and moderately conserved histidine residues (H317A) (Figure S10) which likely act as a base to remove the proton from the substrate hydroxyl group, thereby forming an oxygen anion, and then attacking the sulfo group of PAPS to complete the transfer of the sulfo group. To determine whether these residues play a key role in catalysis, we conducted site directed mutagenesis on residues likely act as a catalytic base (H216A, H317A) or crucial for PAPS binding (K148A, Y247F) 26 . While LGS1 H216A (resulting strain: YSL8f , Table S2) exhibited same activity as wildtype LGS1, replacing LGS1 with LGS1 K148A , LGS1 Y247F , and LGS1 H317A in ECL/YSL8a (resulting strain: YSL8g-i , Table S2) completely abolished the synthesis of 4DO and 5DS (Figure S11), implying that these residues are critical to the catalytic activity of LGS1 (Figure S11).…”
Section: Resultsmentioning
confidence: 99%